Edukasi dan Inovasi Usaha Pengolahan Babyfish Crispy dari Benih Ikan Nila Pada Pemberdayaan Kelompok Wanita di Desa Macang Sakti Musi Banyuasin: Edukasi dan Inovasi Usaha Pengolahan Babyfish Crispy dari Benih Ikan Nila pada Pemberdayaan Kelompok Wanita di Desa Macang Sakti, Kabupaten Musi Banyuasin - Rika Puspita Sari MZ; Muhammad Nizar; Irkhamiawan Ma’ruf; Ade Vera Yani; Idealistuti; Anggun Putri Sabrina (Altifani Journal: International Journal of Community Engagement, 2025)
One of the freshwater fish that has been successfully cultivated by the people of Macang Sakti village is tilapia. However, the high cultivation is not in line with its marketing, which is still relatively low. In addition, high feed costs are also an obstacle to raising tilapia. Therefore, education on innovation in processing tilapia seeds in the form of nutritious food is very necessary to be provided to the community by empowering women's groups as business actors. This effort also aims to increase family economic income. The location of community service was carried out in Macang Sakti Village, Sanga Desa District, Banyuasin Regency, South Sumatra. The methods used were survey methods, counseling, discussion and demonstration (practice) of processing tilapia seeds into crispy babyfish. The implementation of the activity was attended by more than 16 participants from among housewives with great enthusiasm. The results of this Community Service show that community service activities can increase participants' knowledge and skills about nutrition and processing tilapia seeds into healthy snacks (crispy babyfish) and motivate them to actively consume fish.